Trade Tax Through The Electronic System (PMSE) In The Sharia Maqasid Perspective According To Jasser Auda - Nabilah, Deva (Nurani, 2022)
This study aims to analyze Trade Tax Through Electronic Systems based on the perspective of Maqashid Syariah according to Jasser Auda. This research is a library research (library research) through a statutory approach (statute approach) which takes an approach through the perspective of Jasser Auda's maqasid syariah on tax purposes that emphasize the benefit of the people to create social values such as helping fellow people. The type of research data is normative juridical using data collection methods in the form of literature studies by collecting documents and data to be processed using analytical methods. In this study, there are 6 system features, namely cognitive nature, interrelatedness, wholeness, openness, multi-dimensionality and meaningfulness so that it gives rise to the perspective that the principle of tax collection must contain the principles of justice and the benefit of the people in order to bring prosperity and economic prosperity to all people with the principle of openness but on the basis of openness to the world and philosophy. In accordance with the aim of maqasid asy-shari'ah that all forms of effort are to bring goodness and avoid harm (harm).